2016
DOI: 10.1097/md.0000000000003240
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Chemotherapy-Induced Neutropenia at the First Cycle in Invasive Breast Cancer

Abstract: Chemotherapy-induced neutropenia (CIN) was the most apparent side effects of bone marrow suppression with adjuvant chemotherapy. Recently, several studies revealed that CIN may predict better outcomes. However, the researches upon breast cancer were still indefinite.We reviewed the female patients with pathologically diagnosed invasive breast cancer at the First Affiliated Hospital of Wenzhou Medical University, between Jan 2008 and Dec 2010. The lowest neutrophil counts in the second week after the first cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…Finally, we calculated the monocyte/lymphocyte ratio; Figure 1D shows an increase in AMC/ALC during the first NAC cycles followed by a drastic decrease after the 5th cycle, concomitant to the switch in chemotherapeutic drug. Both lymphopenia ( 22 ) and neutropenia ( 23 ) are commonly seen in patients under CT treatment and could explain this decrease.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we calculated the monocyte/lymphocyte ratio; Figure 1D shows an increase in AMC/ALC during the first NAC cycles followed by a drastic decrease after the 5th cycle, concomitant to the switch in chemotherapeutic drug. Both lymphopenia ( 22 ) and neutropenia ( 23 ) are commonly seen in patients under CT treatment and could explain this decrease.…”
Section: Resultsmentioning
confidence: 99%
“…Within the bone marrow microenvironment, hematopoietic stem cells can be differentiated into directional progenitor cells and precursor cells, and finally differentiated or matured into various hemocytes with different functions 38 , including neutrophils and B cells. Studies have shown that lentinan can increase the bone marrow neutrophils in mice with therarubicin-induced myelosuppression 39 , 40 . The antioxidant chlorophyllin enhances bone marrow granulopoiesis, substantially increases peripheral blood neutrophils and further alleviates radiation-induced hematopoietic syndrome 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that CIN may predict favorable prognoses and therapeutic results in some cancers. These studies showed that CIN may be associated with better survival [progression-free survival (PFS) and/or overall survival (OS)] or a lower recurrence risk in breast cancer 1 , gastric cancer 2 , cervical cancer 3 , pancreatic cancer 4 , lung cancer 5 , colorectal cancer 6 , and ovarian cancer patients 7 .…”
Section: Impacts Of Cin On the Clinical Outcomes Of Cancer Patientsmentioning
confidence: 99%